2019
DOI: 10.1017/s0963548318000391
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Threshold for Uniqueness of Solutions to Random Jigsaw Puzzles

Abstract: We consider a problem introduced by Mossel and Ross [Shotgun assembly of labeled graphs, arXiv:1504.07682]. Suppose a random n × n jigsaw puzzle is constructed by independently and uniformly choosing the shape of each "jig" from q possibilities. We are given the shuffled pieces. Then, depending on q, what is the probability that we can reassemble the puzzle uniquely? We say that two solutions of a puzzle are similar if they only differ by a global rotation of the puzzle, permutation of duplicate pieces, and ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Finally in two independent recent works [3,9], it is shown that if q ≥ (2 + )n then the puzzle has unique edge assembly and if q ≥ (n), it has unique vertex assembly. The proofs of Balister, Bollobás, and Narayanan [3] and Martinsson [9] build on the ideas presented in the current paper. In particular the sharper results are obtained by a better analysis of k × k windows.…”
Section: Concurrent and Follow Up Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally in two independent recent works [3,9], it is shown that if q ≥ (2 + )n then the puzzle has unique edge assembly and if q ≥ (n), it has unique vertex assembly. The proofs of Balister, Bollobás, and Narayanan [3] and Martinsson [9] build on the ideas presented in the current paper. In particular the sharper results are obtained by a better analysis of k × k windows.…”
Section: Concurrent and Follow Up Workmentioning
confidence: 98%
“…In particular the sharper results are obtained by a better analysis of k × k windows. However, since the results of Balister, Bollobás, and Narayanan [3], Martinsson [9] involve polynomially large windows they do not provide a polynomial time algorithm for assembly.…”
Section: Concurrent and Follow Up Workmentioning
confidence: 99%
“…We remark that this approach of combining probabilistic and structural elements is very natural and has been applied before, for example, in previous work (see [2,6,16,21]) considering the jigsaw puzzle. For jigsaws, a general approach has been to consider partial reconstructions of the edge-coloring in large "windows" of the form v…”
Section: Theorem 18 Let S(n) Be a Function With S(n) → ∞ And S(n) = O(n) As N → ∞ Then There Exists A Constant C (Which May Depend On S(nmentioning
confidence: 99%
“…Mossel and Ross also considered the problem of reconstructing randomly colored trees, randomly colored lattices in any fixed number of dimensions, and the random jigsaw puzzle problem, in which the edges of the n × n square lattice are randomly colored with q colors, and the problem is to determine for which q it is possible to reconstruct the original jigsaw from the collection of 1-balls. The random jigsaw puzzle problem has since been studied by Bordenave, Feige, and Mossel [6], Nenadov, Pfister, and Steger [21], Balister, Bollobás, and Narayanan [2], and by Martinsson [16].…”
Section: Introductionmentioning
confidence: 99%
“…Remark. After the results in this paper were proved (in November 2016), but before this paper was completed, Martinsson [8], working independently, also announced (in January 2017) a proof of a result analogous to Theorem 1.2 in a very closely related model (and with a more reasonable constant in the 1-statement). We briefly point out that while the respective 0-statements are established in essentially the same fashion both here and in [8], the estimates needed to prove the respective 1-statements are established by quite different approaches.…”
Section: Introductionmentioning
confidence: 96%